Given the polynomial P ( x ) = x 4 + m x 3 − 7 x 2 + n x + p for constants m , n , p such that ( x − 1 ) , ( x − 2 ) , ( x − 3 ) divides P ( x ) .
What is the value of m + n + p ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done. It will be quite handy to know that if P ( x ) is a polynomial, then P ( 1 ) is the sum of its coefficient.
How would you solve it if we replace P ( x ) as x 4 − m x 3 − 7 x 2 + n x + p ? Or reverse any of the signs of the constants?
Changing the signs of constants will still give me m+n+p using P(1) = 0
If the signs of non-constant coefficients are changed, then use the three factors given to get three equations.
eg: Using P(1) = 0 => -m+n+p = 6
Using P(2) = 0 => -8m+2n+p = 12
Using P(3) = 0 => -27m + 3n +p = -18
Then, solve the above three equations to get m, n and p
I had it right in front of me, but I still formed a system of equations between all three solutions of x given :P. It worked, but it took needlessly longer lol.
Synthetic division using 1 leaves remainder of m + n + p - 6 = 0.
Therefore, value = 6.
Problem Loading...
Note Loading...
Set Loading...
As (x-1) is a factor P(x), P(1) = 0
i.e., 1+m-7+n+p = 0
so, m+n+p = 6